Regulation of Temperature on Multitrays in an Indirect Solar Dryer (ISD) with Energy Storage and Three Airflow Modes - G. B. Tchaya; E. Tchoffo Houdji; J. H Tchami; C. Kapseu; M. Kamta (Journal of Engineering)
This work presents the regulation of temperature in an indirect multitrays solar dryer with oriented flux under the irradiance fluctuation. The temperature regulator using a negative temperature coefficient (NTC) as a sensor and fans is designed, and a similar device is also used to measure humidity through a sensor. Inlet and outlet dryer temperature and temperature on the three trays have been recorded with the regulation system according to different airflow modes. Irradiance and humidity have also been recorded. The model of outlet temperature with energy storage was given by using heat transfer equations. The results have shown that in the linking airflow mode, the average temperature on the three trays is 51.3 ± 1.5a°C, 52.18 ± 1.4a°C, and 51.9 ± 1.2a°C, respectively, with 52°C as setpoint temperature and NTC fixed on tray number 2. With temperature sensor in the same tray and 51°C as setpoint temperature, the average temperatures on the three trays are 51.86 ± 1.54°C, 51.60 ± 1.16°C, and 50.42 ± 1.13°C, respectively, in mixed mode, whereas in crossing airflow mode, the temperature gradient does not allow regulation on all trays. The regulation is possible when the temperature in the dryer chamber exceeds the set point temperature by more than 5%. The proportional type corrector is suitable for the temperature controller in indirect solar dryers. When the energy source is unstable, humidity which is a variable parameter is used to mark the end of drying instead of time.